Broken Silence fünf Filme, fünf Länder, fünf Versionen - Puenzo, Luis 1946-; Szász, János 1958-; Čuchraj, Pavel G. 1946-; Łoziński, Marcel 1940-; Jasný, Vojtěch 1925-2019 (Universal Pictures, 2004)
While making "Schindler's List", Steven Spielberg realised that the survivors of the Holocaust were a precious resource in themselves, and that their experiences needed to be preserved in some form. In 1994 he established the "Survivors of the Shoah Visual History Foundation", a non-profit organisation whose charter was to record on video the testimonies of 50,000 Holocaust survivors for posterity, as a teaching resource as well as an historical one. To date some 52,000 testimonies have been recorded in 57 countries around the world. To increase awareness of the Holocaust and to use the material they had collected in a positive way, the Foundation commissioned a series of five films from international film-makers. The charter for each of these directors was to produce an hour-long documentary using pre-recorded testimonies to show the impact of the Holocaust on citizen of their countries. [www.michaeldvd.com.au]